Knowledge and attitudes of physicians and pharmacists towards the use of generic medicines in Bosnia and Herzegovina - Tarik Čatić; Lejla Avdagić; Igor Martinović (Medicinski glasnik, 2017)
Aim: To investigate and assess knowledge and attitudes of pharmacists and physicians towards generic drugs prescription in order to evaluate current trends, obstacles to prescribe/dispense generics and suggest possible improvements of rational and economic prescribing having in mind scarce public budgets for drugs. Methods: A cross-sectional survey among 450 primary care physicians (prescribers) and pharmacists in four major cities in Bosnia and Herzegovina (Sarajevo, Banja Luka, Tuzla and Mostar) during the period between January and March 2016 was conducted. The survey (questionnaire) was developed and physicians’ and pharmacists’ perception was examined using the 5-point Likert scale. Descriptive statistics was used to examine respondents’ characteristics and their responses to survey questions. The respondents perception based on different characteristics was assessed using ordinal logistic regression. Results: Generally, positive attitudes towards generic drugs were found. Majority of respondents, 392 (87.0%) considered generic drugs the same as originators and they could be mutually substituted. Physicians were more likely to prescribe branded drugs, 297 (66.6%), even 391 (86.8%) were aware of generic alternatives. Respondents believed that patients considered generic drugs less effective, 204 (45.4%), and 221 (49.0%) disapproved generic substitution. Conclusion: Our findings suggest that further education and more information about benefits of generic drugs should be provided to key stakeholders including patients. Also, clearer generic drugs policies should be introduced in order to improve generic prescribing and potentially improve access and optimize pharmaceutical public expenditures.
Keywords: drug substitution; practice patterns; economics; policy